Linezolid Is Associated with Serotonin Syndrome in a Patient Receiving Amitriptyline, and Fentanyl: A Case Report and Review of the Literature. (4th March 2013) - Samartzis, Lampros; Savvari, Paraskevi; Kontogiannis, Sofoklis; Dimopoulos, Stavros
Abstract : We report a unique case of an adverse interaction between the oxazolidinone antibiotic linezolid, the tricyclic antidepressant amitriptyline and the opioid analgesic fentanyl in a 68-year-old woman with advanced ischemic peripheral arterial disease and sepsis, under empirical antibiotic treatment. We also summarize the current relevant literature as identified via PubMed, EMBASE, and PsycINFO as well as reference sections of selected articles.